Post-Buckling Spring Vibration Isolator Using Silicone Gel Column: A Theoretical and Experimental Study - Ji-Hou Yang; Xiao-Dong Yang; Qing-Kai Han; Jin-Guo Liu (Applied Sciences, 2021)
Based on the design of a post-buckling silicone gel column (SGC), a novel type of low-frequency vibration isolator is presented, and the vibration isolation performance of this isolator is studied by combining theoretical analysis and experimental verification. The stiffness characteristics of the post-buckling SGC are derived, and its recovery force curves with different parameters are analyzed using two kinds of elliptic integral functions. Displacement transmissibility is formulated using harmonic balance method (HBM), and the influences of the excitation amplitude, damping ratio, SGC section diameter, and Young’s modulus are discussed in terms of the transmissibility. The performance of the SGC system is verified through a series of experimental studies based on the developed experimental prototype. The result shows that the proposed post-buckling spring vibration isolator has a good vibration isolation effect, especially in the low-frequency domain, which may provide a feasible novel design idea for a low-frequency vibration isolator.